Investigating of Some Virulence Genes of Salmonella Isolated From Chickens and Their Eggs Using Biochemical and Molecular Methods - Nada Ali Attallah; Nada Ali Attallah (مجلة الانبار للعلوم البيطرية)
This investigation aimed for isolation and molecularly identify of Salmonella species from local chickens and their eggs. A total of four chicken flocks located inside Baghdad's urban limits provided the 100 cloacal swabs and 100 egg shells used to isolate Salmonella spp. These were cultured on basic medium, then subcultured on XLD then biochemical tests were done for identification of bacteria. PCR was done for confirmation of the results by using the three genes flic, rfbsp,and rfbsg. After t confirming he presence of Salmonella spp., the Kirby-Bauer disc diffusion assay was used to determine susceptibility of antibiotics in all of the isolates (16). The antibiotics that were included in the test were from Bioanalyse in Turkey and included the following: Trimethoprime & Sulphamethoxazole (25 µg), Azithromycin (15 µg), Florfenicol (30 µg), Gentamycin (10 µg), Ciprofloxacin (5 µg), Ampicillin (10 µg), and Tetracycline (30 g). The current results showed that Salmonella spp. was isolated from cloacal swabs at 15% while from egg shell the percentage was 2% and the total percentages of isolation was 8.5%. The genes flic and rfbsg had been were also found in all isolates. The investigation found the following antibiotic resistance rates among the isolates: Azithromycin (82.3%), Florfenicol (70.6%), Trimethoprime- Sulphamethaxezole (70.6%), Tetracycline (64.7%), Ciprofloxacin (58.8%), Ampicillin (52.3%), and Gentamycin (35.3%) Salmonella spp. was isolated significantly from cloacal swabs compared to eggshell which was characterized by multidrug resistance. [AJVS 2024; 17(2.000): 8-16]